Lymphoproliferative disease - An unusual complication - Salvado, M. Catarina; Alberto, M. João; Proença, Rui (Portuguese Journal Internal Medicine, 1997)
The authors present a case of Waldenstrom disease, diagnosed during the study of a hemorrhagic disorder. The appearance of a pneumoperitoneum and a retropneumo-peritoneum led to the diagnosis of a second disease, rarely found in a medical ward.